Design and Fabrication of Thrower Mechanism for Multipurpose Ball Throwing Machine - Gavali, Pankaj B.; Patil, Sujit S.; Ingale, Sanjaykumar M. (Asian Review of Mechanical Engineering, 2022)
The cricket and tennis are one of the popular games in the world. Nowadays the players are trained with the help of practice machine. To simulate different varieties of motions, speeds, and trajectories accurately and repeatedly, practice machine is designed by iterative design processes (manual calculations) with solid works. Two counter rotating wheel mechanism imparts both translational and rotational motions with spin. It is portable, flexible, run-on AC source, operated at various horizontal and vertical planes and desired combinations of both planes. This ball machine was constructed utilizing readily accessible components from the market. Because lowering manufacturing costs is one of the project’s goals, the materials were chosen based on their reduced cost. Furthermore, the machine’s parts are made of recycled and locally sourced materials. Therefore, after building is complete, this machine will be useful to many individuals, especially active gamers. The mathematical analysis for the design of a new tennis ball launcher in order to assess the possibilities for its technical implementation. First, traditional launchers are described. The motion equation of the flying tennis and cricket ball is formulated and numerically solved. This makes it possible to analyze the trajectories of the ball for different initial conditions: elevation angles, velocity of ball. Then, the mathematical analysis of the launcher with two counter rotating rollers is presented.